Effects of ergonomic clip on handles on upper body vibration transmissibility and muscular activity during pedalling with vibrations - Duc, S.; Scholler, V.; Puel, F.; Millour, G.; Bertucc, W. (Journal of Science and Cycling, 2021)
Mountain bikers often report impaired finger sensitivity caused by mechanical vibrations and misalignment between the wrist and the forearm when using traditional (cylindrical) handles. The aim of this study was to evaluate the acute effects of ergonomic clip-on handles that allowed the hand to rest on the medial carpal bone, on muscular activity, vibration transmissibility between the cycle ergometer and body segments, and handgrip strength. Sixteen cyclists performed two pedalling exercises at ~200 W lasting 20 minutes on a cycle ergometer that delivered vibrations under the fork (vertical amplitude: 4-25 mm; frequency: 417 Hz) whilst using cylindrical handles and ergonomic clip-on handles with a randomized order. Compared to cylindrical handles, ergonomic clip-on handles decreased significantly vibration transmissibility to the extensor digitorum, triceps brachii and flexor carpi radialis muscles by 10, 10 and 7%, respectively. The surface electromyography activity of the flexorcarpi radialis decreased by 45%, while that of the triceps brachii increased by 12% (both significantly). Unlike the cylindrical handles, the ergonomic clip-on handles did not involve a significant decrease in the maximal handgrip force after the pedalling exercise. The ergonomic clip-o handles may prevent symptoms of hand-arm vibration syndrome in mountain bikers and could preserve their ability to effectively maneuverand brakethe bike.